Emotional foundations of cognitive control. Issue 3 (March 2015) - Inzlicht, Michael; Bartholow, Bruce D.; Hirsh, Jacob B.
Highlights: Cognitive control can be understood as an emotional process. Negative affect is an integral, instantiating aspect of cognitive control. Cognitive conflict has an emotional cost, evoking a host of emotional primitives. Emotion is not an inert byproduct of conflict, but helps in recruiting control. Abstract : Often seen as the paragon of higher cognition, here we suggest that cognitive control is dependent on emotion. Rather than asking whether control is influenced by emotion, we ask whether control itself can be understood as an emotional process. Reviewing converging evidence from cybernetics, animal research, cognitive neuroscience, and social and personality psychology, we suggest that cognitive control is initiated when goal conflicts evoke phasic changes to emotional primitives that both focus attention on the presence of goal conflicts and energize conflict resolution to support goal-directed behavior. Critically, we propose that emotion is not an inert byproduct of conflict but is instrumental in recruiting control. Appreciating the emotional foundations of control leads to testable predictions that can spur future research.